2016
DOI: 10.1016/j.copbio.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Matrix assisted laser desorption/ionization-mass spectrometry imaging (MALDI-MSI) for direct visualization of plant metabolites in situ

Abstract: Direct visualization of plant tissues by matrix assisted laser desorption ionization-mass spectrometry imaging (MALDI-MSI) has revealed key insights into the localization of metabolites in situ. Recent efforts have determined the spatial distribution of primary and secondary metabolites in plant tissues and cells. Strategies have been applied in many areas of metabolism including isotope flux analyses, plant interactions, and transcriptional regulation of metabolite accumulation. Technological advances have pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 51 publications
1
99
0
1
Order By: Relevance
“…Recently, MALDI-MS imaging made it possible to study lipid spatial distributions in situ directly from tissue sections (Sturtevant et al, 2016). Previous studies utilizing MALDI-MS imaging in oilseeds of cotton, C. sativa, and Arabidopsis demonstrated that lipid molecular species are not distributed equally between different seed tissues (Horn et al, 2012Sturtevant et al, 2017).…”
Section: Spatial Distribution Of Lipidsmentioning
confidence: 99%
“…Recently, MALDI-MS imaging made it possible to study lipid spatial distributions in situ directly from tissue sections (Sturtevant et al, 2016). Previous studies utilizing MALDI-MS imaging in oilseeds of cotton, C. sativa, and Arabidopsis demonstrated that lipid molecular species are not distributed equally between different seed tissues (Horn et al, 2012Sturtevant et al, 2017).…”
Section: Spatial Distribution Of Lipidsmentioning
confidence: 99%
“…These mass spectra can then be searched for the massto-charge ratio (m/z) of ions of interest, and a heat map or matrix-assisted laser/desorption ionization-mass spectrometry (MALDI-MS) image is generated representing the spatial localization of the ions in question. A summary of the MALDI-MS imaging for the in situ visualization of TAG and PC is shown in Figure 2, but for more detailed descriptions, see Horn and Chapman (2014) and Sturtevant et al (2016).…”
Section: Spatial Mapping Of Pc and Tag At The Midpoint Of Seed Lipid mentioning
confidence: 99%
“…Imaging-based mass spectrometry (MS) approaches have emerged as an alternative, or as an addition to these extraction based methods, to provide an additional spatial dimension to metabolomic studies. Matrix-assisted laser/desorption ionization-mass spectrometry imaging (MALDI-MSI) is a powerful analytical technique that enables the spatial mapping of metabolites within intact biological tissues or directly off tissue surfaces (Cornett et al, 2007;Horn and Chapman, 2014;Sturtevant et al, 2016). This analytical technique was pioneered by the Caprioli group in the 1990s in animal systems (Caprioli et al, 1997) and, over the last decade, has been applied to plant systems to great effect (Horn and Chapman, 2014;Korte et al, 2015;Boughton et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, achieving such high resolution requires careful matrix embedding and sample preparation, which may affect tissue structure and localization of biomolecules. Furthermore, the spatial resolution is insufficient to interrogate individual oil bodies (0.05–3 ”m diameter) at this time [24,27]. …”
Section: Introductionmentioning
confidence: 99%